Challenges and opportunities for AMR research in the ASEAN following the One Health approach - Harish Kumar Tiwari; Daniel K.Y. Tan; Chhe Chinda; Duong Nu Tra My; Ha Thi Thu Hoang; Khao Keonam; Luu Quynh Huong; Ly Chanvatanak; Mot Virak; Nguyen Thuy Tram; Nittakone Soulinthone; Pham Duc Phuc; et al. (One Health)
Background: Antimicrobial resistance (AMR) has emerged as a significant global challenge and Southeast Asia with rapid economic and population growth faces substantial challenge in dealing with emerging infectious diseases and antimicrobial resistance. Here we present the recommendations of a workshop that explored the challenges and opportunities for One Health approach towards AMR research in three countries of AEAN, namely, Cambodia, Laos, and Vietnam. Methods: A workshop was organised in Hanoi, Vietnam in August 2023, involving participants involved in AMR research across varied sectors from three participating countries to prioritise the strategies that can be implemented in the region to fructify the One Health approach to tackle AMR. A modified Delphi approach was used to prioritise the top 10 Global Priority Research Questions for the region as developed by the Quadripartite (FAO, WHO, WOAH and UNEP). An iterative process was adopted to map priorities according to their impact and feasibility of application. Results: Collaborative initiatives, such as a common platform for listing the research goals, a web-based surveillance mechanism, and an enhanced AMR awareness curricula were identified as the steps forward. A consensus statement highlighting the critical needs for improved technical and infrastructure capacity, collaboration between sectors, increased funding, and systematic data analysis was drafted. Discussion: The participating countries have National Action Plans guided by the World Health Organization's Global Action Plan on AMR, but limited collaboration between human health and other sectors has impeded the benefits that One Health approach may achieve in the region. The recommendations include the need for improved technical and infrastructure capacity, and data collection across One Health sectors, besides increasing awareness at multiple levels. Conclusion: A collaborative and coordinated effort to apply One Health initiatives for tackling AMR in the ASEAN region is imperative. The workshop formulated a roadmap for future direction by identifying priorities aimed at enhancing collaboration, addressing infrastructure gaps, and contributing to an effective intervention in the fight against AMR in the region.